(3QSGdI aj JYQja QSGdI GdcjfI aj YdGL GdedGQjGs - (3MSjf Hf Ydj Hf SdjeGf GdMfaj, MSjf NhLI,J (B1169 (3g` s
(3ChdgG (B:s
(3SHMGf Gddg GdeOHQ GdMcje agPG JYQja QSGdI QFjS GdGWHGA HeMQhSI GSdGeHhd GOGegG Gdgd OGQ GSdGe TOjOI GdUhdI s
(3BNQgG (B:s
(3hEf JCNQJ YfO GHJOGA GdeQaj Ydi gPG GdYed hdh SGYI gdc Gdbdjd hdG jfab OhGA s
(3Vef eLehY , JQJjHgG (B: 4s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B609s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI eJhSWI s
(3GdfSNI HgG JdhjK s
Keywords: (3eJaQbGJs